2021
DOI: 10.1177/1534734620982238
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Extensive Soft Tissue Defects of Lower Extremity With the Extended Anterolateral Thigh Flap

Abstract: The anterolateral thigh flap is a classic flap used for various reconstruction defects. However, the flap viability of extended large skin paddles (ie, 240 cm2) was doubted by many surgeons. This study reports successful experience of reconstructing extensive soft tissue defects of lower extremity using extended large skin paddles. Twelve consecutive patients who had undergone reconstruction of defects using an extended anterolateral thigh flap were identified. Patient characteristics (age, sex, defect locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…But in our case, bimalleolar defects accompanying the anterior tibial defect created a complex defect like a triangle shape. We thought that trying to cover all defects as almost circumferential wrist and anterior tibial defects with the same flap and reaching the recipient vessels 8 cm superior to anterior defect with a single ALT might be risky in terms of flap perfusion because the extended ALT also has limitations such as perfusion problems, partial flap necrosis, and increased donor site problems due to large tissue harvest (Kim et al, 2022). So, we decided to use double ALT rather than its single extended version and used both long axis of flaps as inverted "T" shape.…”
Section: Discussionmentioning
confidence: 99%
“…But in our case, bimalleolar defects accompanying the anterior tibial defect created a complex defect like a triangle shape. We thought that trying to cover all defects as almost circumferential wrist and anterior tibial defects with the same flap and reaching the recipient vessels 8 cm superior to anterior defect with a single ALT might be risky in terms of flap perfusion because the extended ALT also has limitations such as perfusion problems, partial flap necrosis, and increased donor site problems due to large tissue harvest (Kim et al, 2022). So, we decided to use double ALT rather than its single extended version and used both long axis of flaps as inverted "T" shape.…”
Section: Discussionmentioning
confidence: 99%
“…Local flaps are limited in this situation because there is little expendable donor tissue for large wound coverage. Some authors reported using large flaps, such as anterolateral thigh (ALT) flaps and deep inferior epigastric perforator (DIEP) flaps to reconstruct large wounds 14 , 15 , 16 . However, donor site morbidities may limit the use of these large flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the necessity to warrant a prompt and stable wound healing, often a reconstruction of the tendinous extensor compartment of the foot is also required to give the patient the chance to walk again. The microsurgical anterolateral thigh (ALT) flap has proven to be an effective reconstructive tool in replacing large soft-tissue losses [ 1 ]. Significant advantages characterize the ALT flap as versatility, easy dissection, adequate size to cover large wounds, and an excellent perfusion.…”
Section: Introductionmentioning
confidence: 99%